Eragrostis mexicana (Hornem.) Link subsp. virescens (J. Presl) S.D. Koch & Sanchéz Vega - Carbone, Lucas M.; Jewsbury, Guillermo (2024)
Fil: Carbone, Lucas M. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias, Herbario ACOR; Argentina.